Nicea Council and Nurcholish Madjid on Human Dignity: a Way of Dialog - Derry Cristofer (Fakultas Teologi, Universitas Sanata Dharma, 2025)
One of the discussions in the Council of Nicea was that man was created in the Imago Dei (the image of God). With the presence of Christ as God incarnate, this understanding is further affirmed, that man has sacred value and ultimate goal in relation to God. In line with that, Nurcholish Madjid, who is one of the Islamic figures in Indonesia, also has interesting thoughts about human beings, especially about human dignity. His thinking is based on Islamic teachings about humans being created as representatives of Allah in this world. This theme of human dignity is important, especially when viewed from two perspectives, Catholicism (in the Council of Nicaea) and Islam (in Nurcholish Madjid's thought). The hope is the creation of a dialogue of thought between two different cultures for the sake of creating harmony and mutual understanding. Therefore, this article wants to answer the question of How did Nurcholish Madjid and the Council of Nicea think about human dignity? The author tries to see the connection between the points of thought in the council of Nicaea and the points of thought of Nurcholish Madjid. Using the Appreciative Inquiry and interculturality approach, the author wants to dialogue these two thoughts and find out what things are related to each other. This paper argues that both Nicea and Madjid contribute valuable insights into the discourse on human dignity. This common view can be a way of dialogue between Islam and Catholicism so that harmony can be created in religious life.